8.5k views
13 votes
Evaluate. Use x=-2 y=6
5x-3y

User Kylefinn
by
5.3k points

2 Answers

10 votes

Answer:

-28

Explanation:

Basically, this question is asking you to substitute the variables (x and y in this case) with numbers to solve the equation. Before we solve, let's replace those variables. So, if x = (-2), and y = 6, then:

5(-2) - 3(6).

We need to solve the equation from left to right. But we can't solve for the subtraction yet, because we need to solve for the multiplication first. So:

5 x (-2) = (-10) and 3 x 6 = 18.

Now we can subtract.

-10 - 18 = (-28).

Let me know if you have any more questions, I hope that this helps.

User Petersohn
by
4.9k points
9 votes

Answer:

-28

Explanation:

x=-2 y=6

5x-3y


5(-2) -3(6)
= -10 -18
= -28

User Blackbishop
by
5.1k points